Combined knee osteoarthritis and diabetes is associated with reduced muscle strength, physical inactivity, and poorer quality of life - Seow, Shi Rui; Mat, Sumaiyah; Teoh, Jun Jie; Mohamad Yusup, Amyra; Rajab, Nor Fadilah; Ismail, Intan Safinar; Ajit Singh, Devinder Kaur; Shahar, Suzana; Tan, Maw Pin; Berenbaum, Francis (Medical Journals Sweden, 2024)
Objective: This study delves into the intriguing connection between knee osteoarthritis and diabetes in Malaysia. Specifically, the exacerbation of knee osteoarthritis in the presence of diabetes in terms of symptoms, physical performance, physical activity, psychological status, social participation, and quality of life was discussed. Design: This cross-sectional study recruited adults aged 50 and above by convenient sampling and grouped them into: knee osteoarthritis-diabetes-, knee osteoarthritis+diabetes-, knee osteoarthritisdiabetes+, and knee osteoarthritis+diabetes+. Subjects/Patients: Of 436 recruited participants, 261 (59.8%) participants reported knee osteoarthritis. Methods: Handgrip strength, Timed Up and Go test, 6 Meter Walk Test, and 5 Times Sit to Stand Test were measured using standardized procedures. Six questionnaires were administered for the remaining parameters. Results: Across groups, there were significant differences: 6 Meter Walk Test (p = 0.024), Timed Up and Go test (p = 0.020), and 5 Times Sit to Stand Test (p < 0.001), quality of life (p = 0.009), and physical activity (p = 0.036). Knee osteoarthritis+diabetes+ was independently associated with reduced handgrip strength, 5 Times Sit to Stand Test, quality of life, and physical inactivity after adjustment. Knee osteoarthritis+diabetes-was independently associated with reduced Timed Up and Go test and social isolation. Conclusion: The findings revealed the diabetic knee osteoarthritis subgroup’s unique physical and psychosocial features of reduced muscle strength and physical inactivity. Future studies should investigate whether managing metabolic factors, and enhancing physical activity and strength exercises, can reduce knee osteoarthritis symptoms and disease severity.